(3GdYjfs - (3GdNdjd Hf CMeO Hf YeQh Hf Jeje GdaQGgjOj GdCROj GdjMeOj, CHh YHO GdQMef,J (B170 (3g` s ((3CHh eMeO jhSa eQJVi Ydi CaTGQ s)
(3ChdgG (B:s
(3HGddg fTgO hYdjg fJhcd gPG eG Cdag GdNdjd Hf CMeO ef MQha C H J K bGd djK bGd GdNdjd (B: (3cdGe GdYQH eHfi Ydi CQHYI CUfGa Ydi GdKfGFi hGdKdGKi hGdQHGYi hGdNeGSi s
(3BNQgG (B:s
(3ef HGH GdMQha GdeYJdI , bhdg (B: (3aEf GdCda GdJi ai hSWgG gi ai GdCUd jGA dbdJ (B: (3CjI eDjGI bO CHjJ JeJ GdMQha GdeYJdI HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3LRAGf ai eLdOs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B112s
Keywords: (3GddZIs